2021
DOI: 10.1161/jaha.120.016835
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Evidence‐Based Therapy Use in Insured Patients in the United States With Type 2 Diabetes Mellitus and Atherosclerotic Cardiovascular Disease

Abstract: Background Evidence‐based therapies are generally underused for cardiovascular risk reduction; however, less is known about contemporary patients with type 2 diabetes mellitus and atherosclerotic cardiovascular disease. Methods and Results Pharmacy and medical claims data from within Anthem were queried for patients with established atherosclerotic cardiovascular disease and type 2 diabetes mellitus. Using an index date of April 18, 2018, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 18 publications
3
51
2
Order By: Relevance
“…The finding that only 58.6% of patients in this study were prescribed a statin is considerably lower than a recently published estimate of 74.6% from a database of commercially insured patients in the US. 9 Notably, the rate of overall statin use in this study was similar to findings from a comparable Medical Expenditure Panel Survey population from 2013, which reported that only 52.7% of patients with diabetes and ASCVD were receiving a statin. 19 In this context, these new data raise concerns that despite strengthening of guideline recommendations in the years prior to our study window, 20 there has been minimal progress in increasing the use of these widely available, cost-effective, safe, and proven medications in the general population.…”
Section: Discussionsupporting
confidence: 85%
“…The finding that only 58.6% of patients in this study were prescribed a statin is considerably lower than a recently published estimate of 74.6% from a database of commercially insured patients in the US. 9 Notably, the rate of overall statin use in this study was similar to findings from a comparable Medical Expenditure Panel Survey population from 2013, which reported that only 52.7% of patients with diabetes and ASCVD were receiving a statin. 19 In this context, these new data raise concerns that despite strengthening of guideline recommendations in the years prior to our study window, 20 there has been minimal progress in increasing the use of these widely available, cost-effective, safe, and proven medications in the general population.…”
Section: Discussionsupporting
confidence: 85%
“…In a recently published study including more than 150 000 patients with T2D and ASCVD from the US, only 2.7% were covered by all three CV protective agents which include statins, angiotensin‐converting enzyme inhibitor or angiotensin receptor blocker, and SGLT‐2i or GLP‐1RA 82 . In addition, 37.4% did not receive any CV beneficial agents.…”
Section: Glp‐1ra Patient Selection: Finding the “The Right Patient”mentioning
confidence: 99%
“…Over the last years, the T2D treatment guidelines have frequently been changed and updated, and it can be challenging to keep up with the newest recommendations issued by different organizations 92,93 . Patients with T2D and CVD more frequently encounter a cardiologist and a PCP than a diabetologist 82,94,95 . A global survey among PCPs shows that PCPs are aware of the beneficial CV effect found in some CVOTs, but do not find the clinical implications to be fully clear 83 .…”
Section: Implementing Treatment Guidelines In Non‐specialist Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their overwhelming cardiovascular-renalmetabolic benefit, SGLT2i and GLP1RA were prescribed in only 10.2% of patients with type 2 diabetes mellitus and cardiovascular disease in a large, US-based commercial insurance cohort. 84 In this same cohort,~25% of individuals were on a high-intensity statin,~53% were on angiotensin-converting enzyme inhibitor (ACEi) or angiotensin II receptor blocker (ARB) therapy, and only 2.7% were on all 3 groups of medications: high-intensity statin, angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker, and SGLT2i/GLP1RA.…”
Section: Role Of a Cross-disciplinary Team-based Model For Cardiovascular-renal-metabolic Disease Prevention Among Patients With Type 2 Dmentioning
confidence: 99%